Treatment of bilateral congenital extensor tendon dislocation on multiple digits with only one sagittal band reconstruction: a case report - Lim, Jun-Hyuk; Jung, Sung-Taek; Cheon, Jae Hyeok; Kim, Sungmin (Frontiers in Pediatrics, 2023)
Bilateral congenital dislocation of the extensor tendon in the metacarpophalangeal (MCP) joint is an exceedingly rare disease and often involves multiple fingers. Surgical treatment of multiple congenital extensor tendon dislocations in both hands has been reported; however, no report has clearly stated whether all fingers should be surgically treated in patients with multiple finger involvement. We report a case in which we successfully treated bilateral congenital extensor tendon dislocation on multiple digits with only one single loop reconstruction of the sagittal band instead of operating on all involved fingers.